2021
DOI: 10.1111/ajae.12206
|View full text |Cite
|
Sign up to set email alerts
|

Food Consumption and Food Security during the COVID‐19 Pandemic in Addis Ababa

Abstract: International humanitarian organizations have expressed substantial concern about the potential for increases in food insecurity resulting from the COVID‐19 pandemic. We use a unique panel survey of a representative sample households in Addis Ababa to study both food security and food consumption during the pandemic. In contrast to some other countries in the region, Ethiopia never went into a full lockdown severely restricting movement. Despite subjective income measures suggesting a large proportion of house… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
129
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 142 publications
(139 citation statements)
references
References 32 publications
8
129
0
2
Order By: Relevance
“…Our studies spanned a variety of locations and the timing of the surveys in relation to stringent restrictions varied. Except for the locations where restrictions were mild (Tanzania and Burundi; see also Hirvonen et al, 2021 ), mobility constraints were widespread, as were market access issues, price fluctuations, and income reductions. Almost all households who usually relied upon off-farm incomes reported reductions, on average by a half.…”
Section: Discussionmentioning
confidence: 99%
“…Our studies spanned a variety of locations and the timing of the surveys in relation to stringent restrictions varied. Except for the locations where restrictions were mild (Tanzania and Burundi; see also Hirvonen et al, 2021 ), mobility constraints were widespread, as were market access issues, price fluctuations, and income reductions. Almost all households who usually relied upon off-farm incomes reported reductions, on average by a half.…”
Section: Discussionmentioning
confidence: 99%
“…By contrast, panel data collected in Addis Ababa, Ethiopia, before and during the pandemic, found little change in food insecurity [ 16 ]. Ref.…”
Section: Introductionmentioning
confidence: 99%
“…The pandemic heavily affected the livelihoods of the households in Ethiopia, by which the income is reduced by more than half ( Wieser et al., 2020 ). The subjective income measures indicated that a large proportion of households have been exposed to job loss or reduced incomes during pandemics ( Hirvonen et al., 2021 ). The negative impact of the pandemic will be severe on the welfare of vulnerable households ( Beyene et al., 2020 ).…”
Section: Introductionmentioning
confidence: 99%